1997
DOI: 10.1055/s-2007-972680
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Leisure-Time Physical Activity - a Three Generation Study

Abstract: Studies of parental influence on children's physical activity have had different results. Parental effect on physical activity during adolescence is less studied, and three generation studies have not been carried out. The purpose of our study was to examine intra- and intergenerational associations of leisure time physical activity among family members in three generations. Due to the major changes in society during this time, we also took into consideration the socioeconomic status of the adult subjects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 10 publications
7
50
2
2
Order By: Relevance
“…Statistically, it may conceal the presence of non-additive genetic effects and overestimate the influence of additive genetic factors (Eaves et al, 1989;Cardon & Bell, 2000;Carey, 2002;Heath et al, 1984;Posthuma et al, in press). Assortative mating is known to exist for traits such as intelligence, exercise behavior and body height and weight (e.g., Aarnio et al, 1997;Boomsma, 1998;Vandenberg, 1972), but is to a large extent an unexplored topic in most human populations.…”
Section: Additional Components Of Variancementioning
confidence: 99%
“…Statistically, it may conceal the presence of non-additive genetic effects and overestimate the influence of additive genetic factors (Eaves et al, 1989;Cardon & Bell, 2000;Carey, 2002;Heath et al, 1984;Posthuma et al, in press). Assortative mating is known to exist for traits such as intelligence, exercise behavior and body height and weight (e.g., Aarnio et al, 1997;Boomsma, 1998;Vandenberg, 1972), but is to a large extent an unexplored topic in most human populations.…”
Section: Additional Components Of Variancementioning
confidence: 99%
“…Moreover, from a previous study in Finland, it was found that for both women and men the amount of physical activity at work had decreased over time. 23,24 Finally, even if the total amount of physical activity has decreased in society, WHO recently confirmed that diet is probably the most important factor in the development of obesity. 14 …”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…We will concentrate on general demographic (education), lifestyle variables (smoking, alcohol use, physical activity, coffee-and tea-consumption, religious practice) and personality/ mental health (body mass index, burnout, problem behavior, neuroticism). These variables are familial, that is family members resemble each other for those characteristics [11][12][13][14][15][16][17][18]. Therefore, data from nonrespondents will be correlated with the data from the respondents and data from responding family members thus will offer information on the non-respondents.…”
Section: Introductionmentioning
confidence: 99%